Analisis Pemberdayaan Ekonomi Keluarga Melalui Usaha Budidaya Jamur Tiram (Studi Kasus Reza Jamur Jaya Desa Sei Rotan Kecamatan Percut Sei Tuan Kabupaten Deli Serdang): Studi Kasus Reza Jamur Jaya Desa Sei Rotan Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Lisna R Lubis; Batubara, Chuzaimah; Lestari, Annio Indah (CV. Pusdikra Mitra Jaya, 2024)
Reza Mushroom Jaya is one of the oyster mushroom cultivation businesses managed by Mr. Reza which is located in Sei Rotan Village, Percut Sei Tuan District. Where the oyster mushroom cultivation business is managed by the local community from the Sei Rattan village with the aim of improving the family economy. The formulation of the problem in research is how the process of empowering the family economy in oyster mushroom cultivation in Sei Rotan Village, Percut Sei Tuan District and how the community responds in Sei Rotan Village, Percut Sei Tuan District with the empowerment of this oyster mushroom cultivation business. This study aims to determine whether the Reza mushroom jaya oyster mushroom cultivation business can improve the family economy of the Sei Rotan village community and want to see how the community responds to this oyster mushroom cultivation business. The type of research used is qualitative. The data collection method used primary data and secondary data. Data collection techniques in the form of interviews and documentation. Based on the results of research conducted. With the oyster mushroom cultivation business, it can improve the family economy of the community in the Sei Rattan village, this is seen in terms of education, health and income where the income of the community before the oyster mushroom cultivation business was low and after the oyster mushroom cultivation the community's economy began to improve. From the results of research conducted, the response of the people of Sei Rattan Village to the existence of oyster mushroom cultivation is partly less enthusiastic. But other than that, some people respond positively to this oyster mushroom cultivation business, because with this oyster mushroom cultivation business it can improve their economy.